Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadits di MI Riyadlus Sholihien dan Upaya Mengatasinya - indi, ayudia; Heriani, Ayudia Indi; Contrunada, Camelia; Zawawi, M. Ilmil (STIT Muhammadiyah Bojonegoro, 2026)
This study aims to analyze students’ learning difficulties in the Al-Qur’an Hadith subject at Madrasah Ibtidaiyah and to identify the causal factors and teachers’ efforts to overcome them. This research employed a qualitative descriptive approach conducted at MI Riyadlus Sholihien Jember. The informants consisted of 10 participants, including 2 teachers and 8 students, selected through purposive sampling. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results showed that students experienced learning difficulties in three main aspects: reading Qur’anic verses according to tajwid rules, memorizing learning materials, and understanding the meanings of verses and hadiths. These difficulties are interrelated and contribute to low student learning outcomes. The factors causing these difficulties include internal factors such as low learning interest and motivation, as well as external factors such as less varied teaching methods, limited use of instructional media, and lack of practice at home. The teachers’ efforts to overcome these difficulties include providing individual guidance, applying drill methods, and utilizing learning media such as audio. These efforts have been proven to gradually improve students’ abilities in reading, memorizing, and understanding the material. Therefore, it is necessary to develop more innovative, interactive, and contextual learning strategies, along with supportive learning environments, to enhance the quality of Al-Qur’an Hadith learning effectively.